1998
DOI: 10.1073/pnas.95.23.13531
|View full text |Cite
|
Sign up to set email alerts
|

Topoisomerase II-mediated site-directed alkylation of DNA by psorospermin and its use in mapping other topoisomerase II poison binding sites

Abstract: Psorospermin is a plant natural product that shows significant in vivo activity against P388 mouse leukemia. The molecular basis for this selectivity is unknown, although psorospermin has been demonstrated to intercalate into DNA and alkylate N7 of guanine. Significantly, the alkylation reactivity of psorospermin at specific sites on DNA increased 25-fold in the presence of topoisomerase II. In addition, psorospermin trapped the topoisomerase II-cleaved complex formation at the same site. These results imply t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
32
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 40 publications
7
32
0
1
Order By: Relevance
“…It is therefore conceivable that at least one of these electrophilic moieties is capable of reacting with appropriate nucleophiles in DNA and/or the enzyme component (5,8). Several dicarbonyl compounds and aldehydes can in fact react with DNA at specific sites (9,10) and epoxides can induce DNA damage with a mechanism similar to nitrogen mustards (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore conceivable that at least one of these electrophilic moieties is capable of reacting with appropriate nucleophiles in DNA and/or the enzyme component (5,8). Several dicarbonyl compounds and aldehydes can in fact react with DNA at specific sites (9,10) and epoxides can induce DNA damage with a mechanism similar to nitrogen mustards (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…The reaction was filtered and the precipitate was washed with H 2 O (5 mL) and acetone (2 mL) and collected to yield a diastereomeric mixture of (F)-diol (0.24 g, 96%). (F)-(2VR ,3VR )-4V-t -Butylsilyloxy-1,5-Dimethoxy-3V-Hydroxy Dihydrofuranoxanthone (5). A solution of diol (0.23 g, 0.62 mmol), t-butyldimethylsilylchloride (0.14 g, 0.93 mmol), imidazole (0.13 g, 1.9 mmol), and 4-dimethylaminopyridine (38 mg, 0.31 mmol) in dimethylformamide was heated with a heat gun to f85jC and stirred overnight.…”
Section: General Proceduresmentioning
confidence: 99%
“…It is active against drug-resistant human leukemia lines and AIDS-related lymphoma. 6 We have shown that psorospermin alkylation at specific sites on DNA is greatly enhanced in the presence of topoisomerase II (5), indicating that the abasic sites on DNA and antitumor activity of psorospermin might be related to its specific interaction with the topoisomerase II-DNA complex. It has also been proposed that psorospermin induces DNA strand breaks, abasic sites, and protein-DNA cross-links (6).…”
mentioning
confidence: 99%
“…This cytotoxicity has been attributed to its interaction with topoisomerase II and DNA (19). However, currently, treatment of doxorubicin-resistant 8226 cells with PS-RR has resulted in a significantly enhanced intracellular retention of doxorubicin.…”
Section: Discussionmentioning
confidence: 99%
“…We previously have shown that the alkylation activity of psorospermin is greatly increased in the presence of topoisomerase II, an enzyme that assists in DNA breakage and re-ligation. This increase is due to psorospermin's ability to trap the topoisomerase II–DNA complex in the initial noncovalent binding step of the topoisomerase II catalytic cycle, resulting in topoisomerase II–mediated DNA cleavage (19). Due to its mechanism of topoisomerase II–directed alkylation, psorospermin has been characterized as a novel topoisomerase II poison (18, 19).…”
Section: Introductionmentioning
confidence: 99%